Four‐Terminal Perovskite/Copper Indium Gallium Selenide Tandem Solar Cells: Unveiling the Path to >27% in Power Conversion Efficiency. Issue 12 (9th October 2022) - Feeney, Thomas; Hossain, Ihteaz M.; Gharibzadeh, Saba; Gota, Fabrizio; Singh, Roja; Fassl, Paul; Mertens, Adrian; Farag, Ahmed; Becker, Jan-Philipp; Paetel, Stefan; Ahlswede, Erik; Paetzold, Ulrich W.
Abstract : Over the past decade, the impressive progress in power conversion efficiency (PCE) of organometallic halide perovskite solar cells (PSCs), coupled with their ready integration into tandem solar cells, has led them to approach PCEs of 30% for tandem solar cells with a silicon bottom subcell. However, the complementary technology of perovskite/copper indium gallium selenide (CIGS) tandem solar cells has been thus far unable to reach similar efficiency values. Herein, a further advance in the efficiency of 4T perovskite/CIGS tandems is demonstrated, increasing the PCE up to 27.3% via systematic optimization of the top semitransparent PSC. Improvements in light management through the optimization of anti‐reflection coatings, coupled with the development of transparent conductive oxides that incur very low parasitic absorption are reported. It is revealed that both are crucial for maximizing efficiency and, by utilizing additional optical simulations, a detailed loss analysis that enables us to outline a path toward approaching 30% PCE for 4T perovskite/CIGS tandem devices is developed. Abstract : A 4T perovskite/copper indium gallium selenium (CIGS) tandem with a power conversion efficiency (PCE) of 27.3% is demonstrated, achieved via systematic optimization of the optical properties of the top semitransparent perovskite solar cell. Transparent conductive oxides exhibiting low parasitic absorption are combined with optimal anti‐reflection coatings. Finally, optical simulations are used to develop a detailed loss analysis outlining a path to approach 30% PCE for 4T perovskite/CIGS tandem devices.